(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
This research was written to discover the future trends in new media and social networking .The researchers have taken a personal interest in the developments of Web 2.0 platforms after noticing the impact they have made on society on a global scale as well as in our own daily life. The advances in this technology have altered the way individual users and organizations can communicate with each other. In this study of the social network sites we will concentrate on Facebook and its effectiveness as a tool of marketing in the Saudi population because recently it gained enormous popularity for marketing communications. Facebook especially describes itself as the perfect marketing tool because its developers have created an advertising system which allows businesses to use the information of each Facebook user for targeted advertising. Facebook provides the ideal platform for direct communication between organizations and customers. Marketing on social network sites has to follow new rules and principles and each organization has to clearly determine if social media marketing is appropriate for them or not. Through extensive research and analysis, the researchers intended to find if the Facebook is an effective marketing tool in Saudi Arabia where marketers can reach and influence targeted consumers.